2014
DOI: 10.1111/mec.12646
|View full text |Cite
|
Sign up to set email alerts
|

Low host specificity of root‐associated fungi at an Arctic site

Abstract: In High Arctic ecosystems, plant growth and reproduction are limited by low soil moisture and nutrient availability, low soil and air temperatures, and a short growing season. Mycorrhizal associations facilitate plant nutrient acquisition and water uptake and may therefore be particularly ecologically important in nutrition-poor and dry environments, such as parts of the Arctic. Similarly, endophytic root associates are thought to play a protective role, increasing plants' stress tolerance, and likely have an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
86
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(98 citation statements)
references
References 81 publications
(165 reference statements)
11
86
1
Order By: Relevance
“…Consequently, the report on errors caused by tag switching is rare in metabarcoding studies. Indeed, tag switching is common in multiple sequencing platforms such as Roche/454 (e.g., Blaalid et al 2014;Botnen et al 2014) and Illumina sequencing platforms (e.g., Esling et al 2015;Schnell et al 2015), and even in non-metabarcoding Illumina-based studies (e.g., Kircher et al 2011). Studies showed that up to 16 % and more than 2 % sequence reads had non-compatible tag combinations based on Roche/454 and Illumina sequencing platforms (van Orsouw et al 2007;Schnell et al 2015).…”
Section: Tag Switching (Also Known As Tag Jumping)mentioning
confidence: 99%
“…Consequently, the report on errors caused by tag switching is rare in metabarcoding studies. Indeed, tag switching is common in multiple sequencing platforms such as Roche/454 (e.g., Blaalid et al 2014;Botnen et al 2014) and Illumina sequencing platforms (e.g., Esling et al 2015;Schnell et al 2015), and even in non-metabarcoding Illumina-based studies (e.g., Kircher et al 2011). Studies showed that up to 16 % and more than 2 % sequence reads had non-compatible tag combinations based on Roche/454 and Illumina sequencing platforms (van Orsouw et al 2007;Schnell et al 2015).…”
Section: Tag Switching (Also Known As Tag Jumping)mentioning
confidence: 99%
“…Microbial communities in the Arctic represent the largest reservoir of incompletely described biodiversity adapted to extreme conditions. An important component of Arctic microbial diversity is represented by fungi, and fungi in the Arctic can be found in diverse habitats, such as soil [13], ice [4, 5], cryoconite holes [6], moss [7], dead leaves [8], washed-up and trapped wood [9], and plant roots [1018]. In recent years, Arctic microbial communities have been seriously threatened by climate change, as Arctic ecosystems are experiencing the greatest rates of climate warming on the planet and marked changes have already been observed in terrestrial Arctic ecosystems [19].…”
Section: Introductionmentioning
confidence: 99%
“…Hitherto, the diverse fungal communities were found associated with roots of vascular plants in the Arctic [1018] and the endophytic bacterial communities were also detected in Arctic vascular plants [28]. Only two studies reported on the endophytic fungi associated with above-ground plant tissues (i.e., leaves and stems) in the Arctic, including Dryas octopetala in Svalbard [24], Huperzia selago , Picea mariana , and Dryas integrifolia in the Canadian Arctic [29].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to these traditional studies European Arctic-alpine fungal communities have been studied by high throughput sequencing (e.g. Bjorbaekmo et al 2010, Fujiyoshi et al 2011, Lentendu et al 2011, Geml et al 2012, Botnen et al 2014. Also the Arctic region of Greenland has been relatively well studied mycologically (Borgen et al 2006).…”
Section: Introductionmentioning
confidence: 99%